2018
DOI: 10.1007/s00264-018-3792-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for stiffness after distal humerus plating

Abstract: Patients who had distal humerus fracture should be informed about the risk of elbow stiffness especially in AO type C2-C3 fractures and surgical treatment should be planned without any delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In a retrospectively study, Hong et al [15] examined the heterotopic ossi cation after elbow fracture surgery and reported that the risk of heterotopic ossi cation increased 10.62 times when the time to surgery was more than seven days. In another study, Tunalı et al [11] evaluated risk factors for stiffness after distal humerus plating and found that patients with the time to surgery > seven days were more likely (2.59 times) to suffer elbow stiffness. Similarly, Lindenhovius et al [28] compared the acute and subacute treatment of TTI and showed that earlier management could obtain a better exion arc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospectively study, Hong et al [15] examined the heterotopic ossi cation after elbow fracture surgery and reported that the risk of heterotopic ossi cation increased 10.62 times when the time to surgery was more than seven days. In another study, Tunalı et al [11] evaluated risk factors for stiffness after distal humerus plating and found that patients with the time to surgery > seven days were more likely (2.59 times) to suffer elbow stiffness. Similarly, Lindenhovius et al [28] compared the acute and subacute treatment of TTI and showed that earlier management could obtain a better exion arc.…”
Section: Discussionmentioning
confidence: 99%
“…Specially, in recent years, with the increased knowledge of elbow biomechanics, the advancement of xation techniques, and the application of standardized surgical protocols, the satisfactory outcomes have been reported by many studies [7][8][9]. However, the complication rate after operative treatment of TTI was reported as high as 50% [4,5], especially the elbow stiffness, which obvious impairs the patients' activities of daily living [10][11][12]. Morrey reported that an arc of elbow motion between 30° and 130° is required for 90% of daily activities and loss of 50° arc of motion would result in up to 80% of functional loss [13].…”
Section: Introductionmentioning
confidence: 99%
“…The intercondylar distal humerus fracture was the most severely comminuted and complex pattern among all other fractures. And despite achieving the best anatomical reduction and absolute fixation, this fracture pattern carries the highest risk of post-traumatic joint stiffness and is usually associated with flexion contracture [12]. Poor patient compliance and low threshold to pain tolerance are the important factors limiting the early joint mobilization and thus allowing periarticular fibrosis and flexion contractures.…”
Section: Discussionmentioning
confidence: 99%
“… 10 According to the AO classification, fractures type C2-C3 of subjects who undergo surgery 7 days after trauma have a greater risk of developing elbow stiffness; patients must be informed of the possible failure of the procedure and the possible need for reoperation. 11 …”
Section: Etiopathogenesismentioning
confidence: 99%
“…10 According to the AO classification, fractures type C2-C3 of subjects who undergo surgery 7 days after trauma have a greater risk of developing elbow stiffness; patients must be informed of the possible failure of the procedure and the possible need for reoperation. 11 The evaluation of patients with substantial elbow stiffness, even following well-reduced and stabilized fractures, suggests that the thickening of soft tissues, especially of the capsule, is associated with a reduction in ROM.…”
Section: Etiopathogenesismentioning
confidence: 99%